2012
DOI: 10.1590/s1679-87592012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spartina alterniflora invasion stages on macrobenthic communities on a tidal flat in Wenzhou Bay, China

Abstract: A B S T R A C TMany coastal habitats in eastern China are being substantially altered by the invasion of Spartina alterniflora. The species richness, density, Margalef's diversity index (R) and Shannon's diversity index (H') of macrobenthic communities on a tidal flat in Wenzhou Bay, China, were analyzed with the factors of invasion stage and season, in 2007. A significant effect of invasion stage, season, and the interaction between them on communities was detected. The macrobenthic community was more complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Presently, studies relating to the impact of human activities on the sediment, hydrodynamics and ecological environment of tidal flats have concentrated on (1) artificial reclamation [16][17][18][19][20][21][22], (2) artificial introduction of plants [23][24][25][26], (3) seawall construction and repair [27][28][29] and (4) harbor and wind farm construction [30,31]. Despite significant interest, the effect of artificial seafood cultivation on the geomorphic evolution process has not been sufficiently studied and lacks thorough analysis due to the difficulty of data acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, studies relating to the impact of human activities on the sediment, hydrodynamics and ecological environment of tidal flats have concentrated on (1) artificial reclamation [16][17][18][19][20][21][22], (2) artificial introduction of plants [23][24][25][26], (3) seawall construction and repair [27][28][29] and (4) harbor and wind farm construction [30,31]. Despite significant interest, the effect of artificial seafood cultivation on the geomorphic evolution process has not been sufficiently studied and lacks thorough analysis due to the difficulty of data acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…We observed no differences in biomass among habitats. Ge et al (2012) demonstrated that macrobenthic communities were more complex in initial S. alterni ora invasion patches than in patches at other invasion stages, and that S. alterni ora invasion stage signi cantly affected macrobenthic community structure; their results also indicated higher biodiversity in the initial stage of invasion (1-2 years), decreasing during invasion progress (3-4 years) until completion (5-6 years), perhaps due to S. alterni ora canopy changes.…”
Section: Effect Of Spartina Invasion On Macrobenthic Communitiesmentioning
confidence: 95%
“…C. cingulata and L. scabra are the most common gastropods that can be found in the mangrove habitat in the North Sulawesi area. Gastropod C. cingulata has a very wide distribution and is almost found all over the world and distributed in tidal flat areas (Ge et al, 2015). Extensive previous research that C. cingulata is found in mangrove habitats in various regions in Indonesia such as Pemalang (Puryono and Suryanti, 2019), Aceh besar (Irma and Sofyatuddin, 2012), Tanah besar (Nugroho et al, 2019), and Cilacap (Sugiarto et al, 2021).…”
Section: Gastropods Collectionmentioning
confidence: 98%